Influence of Family Environment on Physical Health of Children and Adolescents - Yongmei, Hou (Disease and Health Research: New Insights Vol. 10, 2024)
Objective: The objective of the study is to explore the impact of family environment on the physical health of children and adolescents. Method: The literature search method was used, with CNKI and Web of Science as the main data sources. Fifty-seven papers were compiled to explain the concepts of physical fitness and family environment. Taking BMI, sleep quality, and physical activity as examples, the impact of the two major aspects of family environment - psychological environment and physical environment - on the physical health of children and adolescents was analyzed. Results: Safe parent-child attachment, democratic parenting style, reasonable dietary management, stable living environment, and nuclear family are more conducive to the normal development of BMI in children and adolescents. Safe parent-child attachment, democratic parenting style, stable and tidy living environment, and nuclear family are more conducive to children and adolescents obtaining good sleep quality. Secure attachment, authoritative parenting style, scientific family sports behavior environment, family physical environment with the low disorder, complete family structure, correct health awareness and exercise behavior of parents are more conducive to the development of children’s and adolescents' sports activities. Conclusion: Family environment is an important influencing factor on the physical health of children and adolescents, and a good family psychological and physical environment can help improve the physical health level of children and adolescents.